Assistance in the Preparation of Scientific Articles in the National Journal for Teachers - Efendi, Agus; Maryono, Dwi; Sujana, Yudianto; Basori, Basori (Jurnal Abdimas, 2023)
Writing scientific papers aims to express ideas, thoughts and information in the form of writing and a writer is able to distinguish between opinions and facts. The purpose of the service is to improve the ability of teacher professionalism by equipping teachers in terms of strategies for compiling scientific papers correctly in accordance with writing guidelines, and equipping teachers in procedures for publishing scientific articles in accredited journals scientific publications for teachers who are prerequisites for promotion and position, so as to motivate teachers to make more quality scientific work. The method of implementing assistance in writing scientific articles includes activity steps that emphasize the learning process. This mentoring activity is built on the basis of active participation (participation) of trainees in all aspects of training activities, starting from planning, implementation, to the assessment stage of learning activities in training. The implementation of assistance in the preparation of scientific articles in the National Journal for teachers of SMKN 1 Sawit Boyolali is divided into three groups of speakers as follows, namely: 1) Format of writing scientific articles 2) Mendeley, 3) Online Journal System. The results achieved in this activity are that teachers have increased the motivation of teachers to write papers, conceptual articles and research articles and can increase the understanding, ability and skills of teachers writing scientific papers. Teachers have a basic understanding of how to identify, select and formulate topics and titles, compile outlines, collect writing materials, organize, and conceptualize writing, as well as scientific writing and editing using mendeley software. 63.6% of teachers have the intentionto write articles in scientific journals. Teachers enthusiastically participate in community service activities that are attended by 100% of the stipulated conditions. Teachers are able to understand the rules and procedures in writing scientific papers, the process of stages in making articles and guidance in publishing articles with the help of mendeley software.